Design and experimental evaluation of a multi-drum magnetorheological brake with side-set dual-coil - Jie Wu; Weiguo Kong; Yuming Huang; Hao Huang (Alexandria Engineering Journal)
Torque density, torque range and response time are the problems to be solved urgently in the field of magnetorheological (MR) transmission. To improve the torque, the most frequently used techniques are increasing the effective area and magnetic field strength of MR fluids, such as multiple gaps and multiple coils designs. This paper proposed a multi-drum MR brake with side-set dual-coil. First, a structure description of the multi-drum MR brake is presented. The torque and torque density models are established. Then, an approximate optimization is conducted to obtain the optimal values for main dimensional parameters. Finally, a brake prototype is manufactured and the performance is validated. Experimental results indicate that the maximum torque is 6.8 N m, and the torque density is 37.866 kN m−2 when the two magnetic fields are superimposed together. Different torque capability and torque density can be gained by controlling the magnitude and direction of input current of the two coils. The results indicate that the torque capacity, torque density and torque range can be improved by the two coils. Furthermore, it can be concluded that the coil current has little effect on the transient time while the rising time is affected by the rotational speed.